Proof of Intersection of a Line and a Circle

Proof of Intersection of a Line and a Circle

Proof of Intersection of a Line and a Circle P2(x2,y2) P1(x1,y1) r C(xc,yc) This problem is most easily solved if the circle is in implicit form: 2 2 2 (x − xc) + (y − yc) − r = 0 and the line is parametric: x = x0 + ft y = y0 + gt Substituting for (parametric line) x and y into the circle equation gives a quadratic equation in t: • Two roots of which give points on the line where cuts the circle. p f(x − x ) + g(y − y ) ± r2(f 2 + g2) − (f(y − y ) − g(x − x ))2 t = c 0 c 0 c 0 c 0 (f 2 + g2) • The roots maybe coincident if the line is tangential to the circle. P1(x1,y1) 1 r C(xc,yc) • If roots are imaginary then there is no intersection. 1 1 Proof: The circle is in implicit form: 2 2 2 (x − xc) + (y − yc) − r = 0 (1) and the line is parametric: x = x0 + ft y = y0 + gt (2) Substituting for (parametric line) x and y from Eqn. 2 into the circle equation, Eqn. 1, gives a quadratic equation in t gives: 2 2 2 (x0 + ft − xc) + (y0 + gt − yc) − r = 0 (3) Let xd = x0 − xc yd = y0 − yc (4) Then we may write Eqn. 3 2 2 2 (xd + ft) + (yd + gt) − r = 0 (5) Expanding the quadratic parts in Eqn. 5 gives: 2 2 2 2 2 2 2 xd + 2fxdt + f t + yd + 2gydt + g t − r = 0 (6) Express Eqn. 6 as a quadratic in t, so gather terms in t in Eqn. 6: 2 2 2 2 2 2 (f + g )t + (2fxd + 2gyd)t + xd + yd − r = 0 2 2 2 2 2 2 (f + g )t + 2(fxd + gyd)t + xd + yd − r = 0 (7) 2 2 Now the general solution of a quadratic of the form ax + bx + c = 0, gives the roots, xi; i = 1; 2 as: p −b ± b2 − 4ac x = (8) i 2a So in our problem (a quadratic in t) from Eqn. 7 we can see that for Eqn. 8: a = (f 2 + g2) b = 2(fxd + gyd) 2 2 2 c = xd + yd − r Substituting for a; b and c in Eqn. 8 we get roots of t, ti: q 2 2 2 2 2 2 −2(fxd + gyd) ± (2(fxd + gyd)) − 4(xd + yd − r )(f + g ) t = i 2(f 2 + g2) q 2 2 2 2 2 2 −2(xd + gyd) ± 4(fxd + gyd) − 4(xd + yd − r )(f + g ) t = i 2(f 2 + g2) (9) The expression of the right hand side of Eqn. 9 can be simplified in a few ways. p Firstly we can factor 4 from the term and the division by 2 then simplifies the equation to: q 2 2 2 2 2 2 −2(xd + gyd) ± 2 (fxd + gyd) − (xd + yd − r )(f + g ) t = i 2(f 2 + g2) q 2 2 2 2 2 2 −(fxd + gyd) ± (fxd + gyd) − (xd + yd − r )(f + g ) t = i (f 2 + g2) (10) 3 p Let us now consider the term and simplify this, let: 2 2 2 2 2 2 S = (fxd + gyd) − (xd + yd − r )(f + g )) 2 2 2 2 2 2 2 2 2 2 2 2 2 2 2 2 S = f xd + 2fgxdyd + g yd − f xd − f yd + f r − g xd − g yd + g r (11) 2 2 2 2 Eqn 11 can be simplified as follows, some terms cancel out f xd, g yd and others can be gathered together r2; f; and g terms: 2 2 2 2 2 2 2 S = r (f + g ) − (f yd − 2fgxdyd + g xd 2 2 2 2 S = r (f + g ) − (fyd − gxd) 2 2 2 2 S = r (f + g ) − (−gxd + fyd) (12) Substituting for xd and yd from Eqn. 4 in Eqn 12 we get: 2 2 2 2 S = r (f + g ) − (−g(x0 − xc) + f(y0 − yc)) 2 2 2 2 S = r (f + g ) − (g(xc − x0) − f(yc − y0)) p Substituting for S from Eqn. 13 and xd and yd from Eqn. 4 in the term in Eqn. 10 gives us the solution: p f(x − x ) + g(y − y ) ± r2(f 2 + g2) − (f(y − y ) − g(x − x ))2 t = c 0 c 0 c 0 c 0 (f 2 + g2) Q.E.D 4.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    4 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us